THE ANALYSIS OF CUSTOMER RETENTION AND CUSTOMER’S EMOTIONAL EXPERIENCE IN LOCAL COFFEE SHOP (CASE STUDY OF NOMAD COFFEE SHOP) - Mamonto, Audinia; Lapian, Joyce S.L.H.V.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2020)
Small and medium micro businesses are currently increasing very rapidly, flown with modernity today which is better at opening up insights and knowledge about the younger generation so many prefer to run their own businesses to become employees, with the help of consequences and hunting that enhances micro business small and medium enterprises continue to grow rapidly. To find out how to retain customer retention and what are the components that build the customer’s emotional experience in local coffee shop. This research used descriptive analysis, in which the method is to explain about the opinions of customers who prefer to enjoy the products offered in micro and small businesses based on their emotion and how according to their retention about the service and product. This study obtained conclusion, from the results of research on people who make purchases on the local coffee shop. Based on the service they have received before and also the products they have obtained from the place of business, while for new customers, they use references from people they trust. Keywords: customer retention, customer emotion, emotional experience